Seasonal Variation of Appendicitis in High Altitude Region of Nepal: Five years’ Experience of a Teaching Hospital - Menyangbo, Suryaman; Bhatta, Gakul; Devkota, Harihar; Neupane, Manik; Rokaya, Poojan; Panta, Prem Prasad (Journal of Karnali Academy of Health Sciences, 2020)
Background: Acute appendicitis is the most common general surgical disease, worldwide. The exact etiology is still in conjecture. However, the inadequate fiber in diet, smoking, mechanical obstruction in appendiceal lumen, has been attributed as factors for appendicitis. Appendicitis presents throughout months of the year, however, incidence increases in particular months. The objective of this study is to observe the appendicitis incidence variation with months of the year in high altitude region of Nepal. Methods: The cross-sectional retrospective study was conducted in the Karnali Academy of Health Sciences, Jumla situated at the altitude above 2500 m from sea level. The clinical data were retrieved from the hospital record book in the Operation Theater that included age, gender, ethnicity, month of the appendectomy executed, pre-operative clinical presentation, and operative findings. The period of study was from July 2014 to March 2020. The data were entered in Microsoft Excel software and descriptive analysis was done to get mean, median percentage, standard deviation by SPSS 16. Results: A total of 119 appendectomies performed during 5 years period, from 2014 to 2020, in the surgery department of Karnali Academy of Health Sciences were recorded. The mean age of appendectomy was 27 years. There were 53% female (n=64) and 46% male (n=55) patients. The months in which the highest appendectomy executed were July/August/September and February with 16% (n=19), 13.4% (n=16), (n=15) 12.6% and 13.4% (n=16) respectively. The lowest incidence was 1.7% in the month of April. Conclusion: The incidence of appendicitis is high in the months from July to September with the lowest incidence is in the months of April and May. This information could be useful to decrease the disease-associated morbidity and mortality as well as it can be useful for hospital administration for enrolling the needed health-workers in those particular time periods.